From isolation to individualism: collegiality in the teacher identity narratives of experienced second-level teachers in the Irish context. Issue 1 (2nd January 2021) - Murray, Clíona
Abstract : Harnessing teacher collegiality has been advocated as a means through which to negotiate contemporary challenges to teacher professionalism. However, the dominance of discourses of competitive individualism in global educational contexts poses a challenge to collegial relationships. This paper draws on the findings of a narrative study of teacher identity in the Irish context. It points to some ambiguities and tensions within the operation of teacher collegiality in that context and highlights the profession's cultural susceptibility to individualism. The paper argues that glossing over these vulnerabilities could hamper the development of collegial professionalism. These findings highlight the importance of bringing a culturally and contextually embedded analysis to the critique of international trends around teacher professionalism.